Starring the Baby-sitters club! - Martin, Ann M., 1955- (New York : Scholastic, 1992)
Kristy is in the starring role as Peter Pan in the school play. The other members of the Baby-sitters Club are involved onstage and off. But when rehearsals start nothing goes right.
5.7
3-6
Keywords: Babysitters -- Fiction; Plays -- Fiction; Babysitters -- Fiction; Drama -- Fiction